Pengaruh Lingkungan Kerja, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada Pt. Wonti Indonesia - Kumala, Alia Noor; Saputro, Arie Hendra (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This research aims to determine the level of influence of the work environment, work motivation and job satisfaction. This research uses quantitative research methods with a descriptive and verification approach. The sample in this study was the total sample with 38 respondents. The results of this research show that: (1) work environment variables partially have no significant effect on employee performance by 37.8%, (2) work motivation variables are partially positive and significant on employee performance by 74.9%, (3) variables Partial job satisfaction does not have a significant effect on employee performance at 34.9%. The results of this research explain that the work environment, work motivation and job satisfaction simultaneously influence employee performance.